CATERING STUDENTS' NEEDS TO PROMOTE AESTHETIC EXPERIENCE IN EFL LITERATURE CLASS WITH REFERENCE TO RESPONSE-CENTRED CURRICULUM - Ishkak Said (Celt: A Journal of Culture, English Language Teaching & Literature, 2013)
The success of literature instruction is dependent upon not only the teaching strategies, but also the well-developed curriculum, which accommodates student needs. Teaching practice of literature in the multicultural contexts has to do with teachers' belieft in approaching to their day-to-day practice endowed in the curriculum they are concerned with. In this respect, the existing literature curricula should ideally reflect aesthetic experiences that enhance students' freedom and enjoyment with literary works assigned The present study examines how three case High School English teachers from different sites with different multicultural entities in West Java, Indonesia, developed literature curricula in such a way that their students got 'free room' to express what they wanted and needed to say and to do. Following the traditions of a qualitative multi-case and -site study, the present study investigated the process of teaching literature in language studies streams of the three sites by occupying classroom observation and interview, and administering questionnaires as well. The findings revealed that, in their classroom practices, the three cases endeavored to cater their students' needs through developing negotiated response-based literature curriculum that led to varied and unique activities in the forms of celebrations showing their personal engagements in responding to.Jiterature assigned. Yet, their different schooling systems and contextual factors, and the subjects' perspectives in literature pedagogy and their lived-through literary. reading experiences, have made each case indicate typical and unique phenomena, which is in accordance with the spirit of school-based curriculum.